Mosby's diagnostic and laboratory test reference - Pagana, Kathleen Deska, 1952-; Pagana, Timothy James, 1949-; Pagana, Theresa Noel (St. Louis, Missouri : Elsevier, 2023)
Perform today's important lab tests safely and accurately! With test entries organized the way you'll use them, Mosby's® Diagnostic & Laboratory Test Reference makes it fast and easy to look up current testing information. Concise monographs are arranged alphabetically and include vital information such as the type of test, alternate or abbreviated test names, test explanation, normal and abnormal findings, possible critical values, contraindications, potential complications, interfering factors, and guidelines to patient care before, during, and after the test. From the experienced author team of Kathleen Deska Pagana, Timothy J. Pagana, and Theresa Noel Pagana, this bestselling handbook offers a compact size, durable cover, and A-to-Z thumb tabs for quick reference while on the job --
Includes index.
Keywords: Diagnosis, Laboratory -- Handbooks, manuals, etc; Medical laboratories -- Handbooks, manuals, etc; Handbooks and manuals